Create, produce, consume : new models for understanding music business - Bruenger, David, 1953- (University of California Press, 2019)
"Music usually begins as an idea or a feeling. Understanding how or why is a mystery beyond the scope of this text. Instead, we will take musical creation as a given and focus on what comes after: shared musical experience, what makes it happen, and the forms of value it can generate. Musical experience depends upon someone making and someone else listening to music. Performance can be technologically mediated so that performer and listener don't need to be in the same space at the same time. Or the performer and listener can be in the same room (or even be the same person). But for music to have wider impact, the minimum "equation" is one performer plus one listener equals a musical experience. How music moves from an idea--creation--to the ears of listeners--reception--is where the production structures of music enterprise come into play. All forms of music production provide access to musical experience, regardless of venue or technological medium. Access to music and musicians is what brings music commerce, community, and culture to life. Consequently, managing access and the complex relationship between artist and audience is the essential mission of every music enterprise, regardless of where or when or in what genre it happens"--Provided by publisher